2022
DOI: 10.1177/11206721221144656
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of visual and refractive results after wedge resection for high astigmatism after penetrating keratoplasty in keratoconus

Abstract: Purpose To analyze visual and refractive results after wedge resection to correct high astigmatism after penetrating keratoplasty (PK) for keratoconus. Setting Cornea Unit of the Centro de Oftalmología Barraquer Barcelona, Spain. Design A retrospective quasi-experimental, before and after study. Methods Patients who developed high astigmatism or ectasia in the graft-host junction after PK were treated with wedge resection. The following variables were studied before the surgery, 1-year after and at the final v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Penetrating keratoplasty (PK) is a traditional full-thickness corneal transplant surgery typically reserved for advanced KCN [ 65 ] . A retrospective study suggested that wedge resection is secure and effective for correcting astigmatism resulting from ectasia in the graft-host junction after PK for KCN [ 67 ] . It reduces refractive astigmatism, improves visual acuity, and has moderate efficacy [ 67 ] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penetrating keratoplasty (PK) is a traditional full-thickness corneal transplant surgery typically reserved for advanced KCN [ 65 ] . A retrospective study suggested that wedge resection is secure and effective for correcting astigmatism resulting from ectasia in the graft-host junction after PK for KCN [ 67 ] . It reduces refractive astigmatism, improves visual acuity, and has moderate efficacy [ 67 ] .…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study suggested that wedge resection is secure and effective for correcting astigmatism resulting from ectasia in the graft-host junction after PK for KCN [ 67 ] . It reduces refractive astigmatism, improves visual acuity, and has moderate efficacy [ 67 ] . Therefore, it can be an initial choice for managing high astigmatism [ 67 , 68 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Data from de Oteyza et al (11) shows that the average refractive astigmatism decreased from 11.47± 3.57 to 4.79 ± 3.32 diopters (D) during the pre-and postoperative periods, respectively (p <0.001).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, visual acuity often remains unsatisfactory [ 33 ]. Other approaches mentioned in the present study include surgical procedures such as suture tightening or selective suture removal as well as novel blunt dissection technique [ 5 ], intracorneal ring segments (ICRS) including Ferrara-type ICRS implantation [ 14 , 22 ], femtosecond laser-assisted ICRS implantation [ 13 , 14 , 19 , 24 , 34 ], relaxing incisions [ 23 ], corneal wedge resection [ 12 , 18 ], photorefractive keratectomy (PRK) [ 17 ], and deep intrastromal arcuate keratotomy with in situ keratomileusis (DIAKIK) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“… Forest plot for visual acuity change using fixed- and random-effects model [ 5 , 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 ]. …”
Section: Figurementioning
confidence: 99%